1992
DOI: 10.1203/00006450-199208000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Copper Status of Very Low Birth Weight Infants during the First 12 Months of Infancy

Abstract: ABSTRACT. The Cu intake and status of 106 very low birth weight (VLBW) infants (birth weight 1152 ± 251 g, gestational age 29 ± 3 wk, mean ± SD) were determined approximately 1 mo before hospital discharge, at discharge (time 0), and at 3, 6, 9, and 12 mo ± 3 wk corrected for gestational age. Infants were fed either formula plus supplemental Zn/Cu (SUPPL, n = 29); formula plus placebo (PLAC, n = 26); or a low birth weight formula (LBWF, n = 26) or were breast-fed (BRMLK, n = 25).Plasma Cu levels in the formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Copper is [41]. A deficiency of either Fe or Cu will result in anemia, namely, Fe deficiency anemia or Cu deficiency anemia.…”
Section: Resultsmentioning
confidence: 98%
“…Copper is [41]. A deficiency of either Fe or Cu will result in anemia, namely, Fe deficiency anemia or Cu deficiency anemia.…”
Section: Resultsmentioning
confidence: 98%
“…In a recent longitudinal study, LBW infants had compromised Cu status (as assessed by low erythrocyte CuZn‐superoxide dismutase (CuZn‐SOD) activity) that persisted through the 100 days tested and this was associated with increased oxidative damage to DNA [52]. LBW infants with the largest weight gains in the first 6 months of life are characterized by low erythrocyte SOD activity indicating that the potential for Cu depletion may be higher in rapidly growing LBW infants [53]. Additionally, LBW infants receiving high Fe supplements show low erythrocyte SOD activity, which reflects altered Cu metabolism [54].…”
Section: Secondary Cu Deficienciesmentioning
confidence: 99%
“…Indeed, van Zoeren-Grobben reported that infants fed human milk had higher plasma trapping ability, a measure of resistance to oxidative stress in vitro, than did control infants who were formula fed (15). This may be due to the presence of antioxidant enzymes glutathione peroxidase (GPx), catalase (Cat), and superoxide dismutase (SOD) present in human milk, but not in formula (16), which in addition to their antioxidant effect in the gut may pass through the porous neonatal intestine early in infancy (13).…”
mentioning
confidence: 99%